Efforts of DPPA in Palembang to Provide Early Psychological Support for Teenage Victims of Digital Sexual Violence - Pirdasyah, Rizki Dian Meira; Tama, Mulia Maritas Lasutri (International Journal Scientific and Professional, 2025)
Background: Cases of violence against children and women, especially sexual violence, are still a serious problem. The psychological impact of cases like this cannot be considered trivial. Victims can experience excessive anxiety, depression, guilt, and loss of self-confidence. Early Psychological Support (EPS) or Psychological First Aid (PFA) is an initial approach to help individuals experiencing crisis, trauma, or emotional distress. Methods: The approach used in this report is a descriptive qualitative approach to understand the outpatient rehabilitation process in depth. This research was conducted at the Department of Women's Empowerment and Child Protection of South Sumatra City. The intervention used in this case study was Early Psychological Support (EPS) intervention on sexual violence victims. Data collection was carried out in three ways: Participatory Observation, Case Study, and Documentation. The analysed data were in the form of documents resulting from CBT interventions. Result: Early Psychological Support (EPS) intervention conducted by DPPPA showed that the subject experienced significant positive changes. After receiving the intervention, the subject began to dare to open up and share his feelings with his closest friends. He also took a firm step by deleting his old Instagram account, which was previously associated with a traumatic experience. This behavioural change demonstrates the effectiveness of EPS in facilitating the subject's psychological recovery process. Conclusion: Early Psychological Support (EPS) provided by the Palembang City DPPPA has proven effective in helping recovery process. A collaborative approach between the school and the DPPPA was a key factor in the successful handling of this case